2019
DOI: 10.1177/0003702818805499
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Cation–Anion Interactions in Magnetic Ionic Liquids as Revealed Using High-Pressure Fourier Transform Infrared (FT-IR) Spectroscopy

Abstract: Magnetic ionic liquids are a group of magneto-responsive compounds that typically possess high ionic conductivities and low vapor pressures. In spite of the general interest in these materials, a number of questions concerning the fundamental interactions among the ions remain unanswered. We used vibrational spectroscopy to gain insight into the nature of these interactions. Intramolecular vibrational modes of the ions are quite sensitive to their local potential energy environments, which are ultimately defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The data presented in Table and Figure provide a comprehensive overview of the magnetic properties of various ILs, including their molar magnetic susceptibility (χ m ), mass magnetic susceptibility (χ g ), magnetic susceptibility (χ), and effective magnetic moment (μ eff ). The effective magnetic moment of the iron paramagnetic ILs aligns with previous reports, suggesting the presence of five unpaired electrons . This is consistent with the electronic configuration of Fe 3+ (3d 5 ), which indeed has five unpaired electrons.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The data presented in Table and Figure provide a comprehensive overview of the magnetic properties of various ILs, including their molar magnetic susceptibility (χ m ), mass magnetic susceptibility (χ g ), magnetic susceptibility (χ), and effective magnetic moment (μ eff ). The effective magnetic moment of the iron paramagnetic ILs aligns with previous reports, suggesting the presence of five unpaired electrons . This is consistent with the electronic configuration of Fe 3+ (3d 5 ), which indeed has five unpaired electrons.…”
Section: Resultssupporting
confidence: 90%
“…The effective magnetic moment of the iron paramagnetic ILs aligns with previous reports, suggesting the presence of five unpaired electrons. 24 This is consistent with the electronic configuration of Fe 3+ (3d 5 ), which indeed has five unpaired electrons.…”
Section: Verification Of Evan's Methods Measurement By Accounting For...supporting
confidence: 80%
“…All of these bands gradually shift to higher frequencies as the pressure is increased from 0.7 to 2.5 GPa. These spectroscopic changes indicate phase transformation occurs between 0.4 and 0.7 GPa [ 12 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the analysis of the crystal structure of [C 2 C 1 im][FeCl 4 ] revealed that the C2−H bond does not interact with the [FeCl 4 ] − anion. 68 Based on the infrared spectrum analysis, it appears that the key bands are associated with the C4−H and C5−H bonds, possibly due to the acidic Lewis character of the [FeCl 4 ] − anion. 15 The elongation of the imidazolium cation and the replacement of the halide atom in the anion structure have also been investigated.…”
Section: Anion-based Milsmentioning
confidence: 99%
“…Its imidazolium cation is generally considered unpopular due to the presence of the C2–H bond (see Figure ), which is the most acidic site in the imidazolium ring and prone to forming H-bonds with the anions. However, the analysis of the crystal structure of [C 2 C 1 im]­[FeCl 4 ] revealed that the C2–H bond does not interact with the [FeCl 4 ] − anion . Based on the infrared spectrum analysis, it appears that the key bands are associated with the C4–H and C5–H bonds, possibly due to the acidic Lewis character of the [FeCl 4 ] − anion …”
Section: Magnetic Ionic Liquids Structure and Properties: Insights Fr...mentioning
confidence: 99%